Challenges Facing Arabic Language The Problem of Scientific Terms As A Model - Abdelfattah Farah Daw Ahmed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research deals with the problem of the scientific terms in the Arabic language. In its first topic, it briefly deals with some challenges that the Arabic language faces. One of these challenges is the scientific terms, which is an issue of different aspects. In the second topic, the research deals with the problem of scientific terms in the modern Arabic language[LXC1] . The most important results of the research are as follows: There are plenty of scientific terms in the Arab linguistic heritage. Scientific terms are an example of the language’s ability and capacity to absorb what is new. Scientific terms are a civilized linguistic issue. They have a political dimension that requires the cooperation of the countries of the Arab world in its formulation. They have a close connection with the language of university education. Therefore, it is necessary to make use of the Arabic scientific terms in university education courses since they are a tool for knowledge. Their development and growth are linked to the growth and development of knowledge. The formation of the scientific terms in Arabic must be according to the following steps: Translating the term into another Arabic equivalent, derivation, and generation (i.e. introducing a new term that corresponds with the foreign term) or borrowing, which is either verbal Arabization or localization